Propagation loss measurements for low frequency sonar in Emerald Basin and Exuma Sound - Pecknold, Sean; Theriault, James; Hazen, David (Canadian Acoustics, 2002)
Propagation loss measurements for low frequency sonar in Emerald basin and Exuma sound was presented. A low-frequency hyperbolic frequency modulated signal (HFM) was employed to measure propagation loss in both a deep water environment and in a shallow water surface duct environment. The shallow water measurements indicated that loss of signal coherence increases the propagation loss measured, in this case by 5 dB to 10 dB over this range.